The Mediating Role of Stress-Coping Strategies on the Relationship between Thinking Styles and Mental Health of Nursing and Midwifery Students - Mahin Esmaeili Darmian; Seyyed Vahid Javadi (Mashhad University of Medical Sciences, 2019)
Background & aim: Mental health of medical students is important for working in clinical settings; therefore, it is necessary to know effective mediators in mental health. This study aimed to investigate the mediating role of coping strategies on the relationship between the thinking styles and mental health of nursing and midwifery students. Methods: In this descriptive correlational study, a total of 180 nursing and midwifery students were selected from Islamic Azad University of Birjand, Iran in 2018. Data were collected using valid and reliable questionnaires including personal and social date, general health, as well as thinking styles and coping strategies of Lazarus-Folkman. The questionnaires were completed on a self-report basis by the students. Data were analyzed by AMOS software 20 version and statistical tests, including t-test and correlation matrix. Results: Legal thinking did not have a significant effect on mental health through a problem-oriented strategy (P=0.217); however, it had a significant negative relationship with mental health through an emotional-oriented strategy (P=0/006). The executive thinking had a positive effect on mental health through a problem-oriented strategy (P<0.001), and a negative relationship with mental health through an emotional-oriented strategy (P<0.001). Furthermore, judicial thinking had a positive effect on mental health through a problem-oriented strategy (P=0.046), and a significant negative relationship with mental health through an emotional-oriented strategy (P=0.048). Conclusion: Thinking styles had a meaningful relationship with the mediation of coping strategies with mental health. Emotion-Oriented and problem-oriented strategies created negative and positive relationships between thinking styles and mental health of the students, respectively.